Impact of Advanced Radiotherapy on Second Primary Cancer Risk in Prostate Cancer Survivors: A Nationwide Cohort Study - Jahreiß, Marie-Christina; Heemsbergen, Wilma D.; van Santvoort, Bo; Hoogeman, Mischa; Dirkx, Maarten; Pos, Floris J.; Janssen, Tomas; Dekker, Andre; Vanneste, Ben; Minken, Andre; Hoekstra, Carel; Smeenk, Robert J.; et al. (Frontiers in Oncology, 2021)
Purpose External Beam Radiotherapy (EBRT) techniques dramatically changed over the years. This may have affected the risk of radiation-induced second primary cancers (SPC), due to increased irradiated low dose volumes and scatter radiation. We investigated whether patterns of SPC after EBRT have changed over the years in prostate cancer (PCa) survivors. Materials and Methods PCa survivors diagnosed between 1990-2014 were selected from the Netherlands Cancer Registry. Patients treated with EBRT were divided in three time periods, representing 2-dimensional Radiotherapy (RT), 3-dimensional conformal RT (3D-CRT), and the advanced RT (AdvRT) era. Standardized incidence ratios (SIR) and absolute excess risks (AER) were calculated to estimate relative and excess absolute SPC risks. Sub-hazard ratios (sHRs) were calculated to compare SPC rates between the EBRT and prostatectomy cohort. SPCs were categorized by subsite and anatomic region. Results PCa survivors who received EBRT hadan increased risk of developing a solid SPC (SIR=1.08; 1.05-1.11), especially in patients aged <70 years (SIR=1.13; 1.09-1.16). Pelvic SPC risks were increased (SIR=1.28; 1.23-1.34), with no obvious differences between the three EBRT eras. Non-pelvic SPC were only significantly increased in the AdvRT era (SIR=1.08; 1.02-1.14), in particular for the 1-5 year follow-up period. Comparing the EBRT cohort to the prostatectomy cohort, again an increased pelvic SPC risk was found for all EBRT periods (sHRs= 1.61, 1.47-1.76). Increased non-pelvic SPC risks were present for all RT eras and highest for the AdvRT period (sHRs=1.17, 1.06-1.29). Conclusion SPC risk in patients with EBRT is increased and remained throughout the different EBRT eras. The risk of developing a SPC outside the pelvic area changed unfavorably in the AdvRT era. Prolonged follow-up is needed to confirm this observation. Whether this is associated with increased irradiated low-dose volumes and scatter, or other changes in clinical EBRT practice, is the subject of further research.